Issues and Challenges in Nepalese English Writing - Keshav Raj Chalise (Kaumodaki: Journal of Multidisciplinary Studies, 2025)
Nepalese English writing has followed a global trend of modernity, with a central role, since the political changes of the 1950s. It has changed, especially with the advent of Laxmi Prasad Devkota as a precursor of it. Having no long history, it has emerged along with the introduction of English education and has served as a bridge to global literature. Initially, it was designed to be used by the elites only, during the Rana regime. However, it has held ground now, as the central tenet of English Writing in Nepal/Nepali authors. It has endured many modes of its history. This article attempts to examine the history of Nepalese English writing, its trends, and the issues and challenges it has been facing for a long. It follows the theory of historical observation as the tool and examines the writings of previous writers as the foundation to set a departure. The observation involves the trend of writing in English, both, creation and translation. It will mark a milestone in the historical observation of the writing trends in Nepalese English writing, especially in unearthing the issues and challenges of writing in English with Nepali context and content.